Optimizing ESP Learners' English Vocabulary Proficiency through Mobile-Assisted Formative Assessment - Dwita Laksmita Rachmawati (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2025)
The integration of mobile technology in English language learning has opened new opportunities for formative assessment, especially in ESP (English for Specific Purposes) contexts. This study investigates how Mobile-Assisted Language Learning (MALL) tools can optimize the English proficiency of economics students enrolled in an ESP course at a private university in East Java. This quasi-experimental study involved 30 second-semester students from the Faculty of Economics. The intervention included the use of Quizizz for vocabulary and reading quizzes, Google Forms for writing tasks with feedback, and Padlet for collaborative peer assessment. Pre-test and post-test data were collected over eight weeks and analysed quantitatively using descriptive statistics and paired sample t-tests. The results showed a significant improvement in learners’ vocabulary, reading, and writing scores. Students also reported positive perceptions of the MALL tools in terms of engagement, accessibility, and relevance to their field. The integration of MALL-based formative assessment facilitated feedback cycles, increased learner autonomy, and contextualized ESP instruction. Challenges included varied digital readiness and inconsistent peer feedback participation. This study suggests that MALL can be a scalable and effective strategy for enhancing ESP instruction in non-English departments. Institutions should support teacher training and infrastructure to maximize its potential.